A dual pathway of student motivation: Combining an implicit and explicit measure of student motivation - Lisette Hornstra (Frontline Learning Research, 2018)
Abundant research in social psychology shows human behaviour is guided by beliefs through two pathways, a deliberate and automatic pathway. Research on student motivation has thus far focused mostly on the deliberate pathway and consequently almost exclusively relied on explicit measures (i.e. self-reports of motivation) to assess student motivation and subsequently predict student behaviour and achievement. The purpose of this study was to examine whether student motivation is associated with students’ behavioural engagement and school grades through dual pathways by assessing motivation with a newly developed implicit measure and an explicit measure. Participants were 139 students in year 3 of secondary education (58% female, M = 14.8 years). Motivation was assessed with an implicit association test (IAT) as well as an explicit measure (self-report). Behavioural engagement was assessed by teacher ratings, and school grades were reported by students. The explicit and implicit measures of student motivation were not significantly correlated, suggesting that both measures tap into different aspects of student motivation. Furthermore, structural equation analyses revealed that students’ explicit and implicit motivation were positively associated with school grades. Neither motivation measure was associated with teacher ratings of behavioural engagement. This study contributes to existing research by showing that an implicit measure of student motivation can predict unique variation in school grades in addition to an explicit measure. As such, the current study provides initial support for a dual pathway model of student motivation.